Tradisi Jeguran Pada Peringatan Malam Satu Syuro Di Desa Kajen Kab. Pati - Mochammad Luthfy Bachtiar; Maulfi Syaiful Rizal (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
This paper was compiled and created to study and analyze the implementation process and religious values ​​contained in the jeguran tradition at the first syuro night commemoration in Kajen village, Kab. Pati. The method used in this study is descriptive qualitative with an ethnographic approach. Data collection techniques in this study through observation and interviews. The research subject is the jeguran tradition at the first syuro night commemoration in Kajen village, District Pati. The object of research is the people in the village of Kajen, District Pati. The results in this study found that this tradition had prior preparation in its implementation. Preparation begins with a committee meeting, reading prayers, and draining the pond which is used as a ritual place to be filled with clean water. Then the implementation is carried out after isya or around 19.00 WIB until midnight alternating between children and adults. There are religious values ​​contained in this tradition, including monotheistic values, worship values, integrity values, struggle values, trust values, brotherhood values, and Islamic boarding school values ​​(simplicity, humbleness, and patience).